Mathematical Literacy Based On Entrepreneurial Character Students on Problem Based Learning Nuance of Mathematics In Context - Endramawati, Tyas Ayun; Mastur, Zaenuri; Mariani, Scolastika (Universitas Negeri Semarang, 2019)
This study aims to determine the effectiveness of Problem Based Learning with the nuances of Mathematics in Context on mathematical literacy and describe mathematical literacy in terms of the entrepreneurial character of students. This study uses a mixed method with concurrent embedded. Subjects of this study were Xth grade students of SMK Pelayaran Semarang 2017/2018 school year. The subject of the study was based on the categories of students' initial entrepreneurial character, namely students with the characteristics of high, middle and low entrepreneurs. Qualitative data were analyzed by the average completeness test, classical completeness test, average difference test and improvement test. Quantitative data were analyzed using data triangulation techniques. The results of the study show that Problem Based Learning with nuances of Mathematics in Context is effective for students' mathematical literacy. Students with high entrepreneur character can achieve indicators of Communication, Mathematising, Representation, Reasoning and Argument and Devising Strategies for Solving Problems, although indicators Using mathematics tools and Using symbolic, formal, and technical language have insignificant errors.